Supply Chain Risk Management in Manufacturing Small and Medium Enterprises: A Systematic Literature Review - Pungula, Vusumuzi (University of the Witwatersrand, Johannesburg, 2024)
Background: Small and Medium Enterprises (SMEs) are becoming major actors in the manufacturing sector due to the rising complexity of global supply chains. However, they still face enormous risks from supply chain disruptions and market dynamics, which can have costly effects. SMEs sometimes lack the means and expertise to execute comprehensive risk management plans intended for larger businesses, despite their significance. Research on Supply Chain Risk Management (SCRM) specifically for small and medium-sized enterprises (SMEs) is noticeably lacking, especially in the manufacturing sector. Purpose: The aim of the study was to systematically review how SCRM has been developing in manufacturing SMEs globally over the past two decades, and provide insights for policymakers, industry associations, and SMEs themselves. Method: A Systematic Literature Review (SLR) was conducted by utilizing a qualitative research approach. Seven key phrases were formulated to guide the search for relevant articles published between 2000 and 2023. A thorough screening process was employed to select 38 articles that met inclusion criteria, and data analysis was performed using NVivo software on these articles. Following this, thematic analysis and textual narrative synthesis methods were employed for data analysis and synthesis. The discussion of the identified themes provides comprehensive insights to policymakers, industry associations, and SMEs into the current status of SCRM research in manufacturing SMEs globally. It highlights the importance of effectively addressing risk variables, developing tailored SCRM approaches, and striking a balance between risk reduction efforts and strategic opportunities within supply chains to enhance resilience and ensure operational continuity. Results: The review revealed a significant increase in SCRM research pertaining to manufacturing SMEs over the past decade. Trends analysis indicated a growing emphasis on SCRM in various disciplines, highlighting its increasing significance. Thematic analysis identified eight key themes, including the current status of SCRM research and factors influencing SCRM strategies in manufacturing SMEs. Conclusion: Based on the comprehensive review of literature, several key conclusions can be drawn. There is prevalent recognition of the importance of SCRM within SMEs, emphasizing the need for proactive risk mitigation strategies tailored to the SME context. While formal risk management approaches are increasingly adopted, the context-specific nature of risk management practices highlights the importance of tailored approaches. Technological advancements play a significant role in enhancing SCRM strategies, alongside the integration of green supply chain management practices.
A research report submitted in fulfillment of the requirements for the Master of Science in Engineering, In the Faculty of Engineering and the Built Environment , School of Mechanical, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Supply chain risks; Manufacturing SMEs; Supply chain risk management; SCRM in manufacturing; enterprises; Risk management in SMEs; SCRM in SMEs; SDG-8: Decent work and economic growth